2015
DOI: 10.1002/ange.201507494
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Allylic Alkylation with Diarylmethane Pronucleophiles: Reaction Development and Mechanistic Insights

Abstract: Palladium-catalyzed allylic substitution reactions are among the most efficient methods to construct C À Cbonds between sp 3 -hybridized carbon atoms.I nc ontrast, muchl ess work has been done with nickel catalysts,p erhaps because of the different mechanisms of the allylic substitution reactions. Palladium catalysts generally undergo substitution by a"soft"-nucleophile pathway, wherein the nucleophile attacks the allyl group externally.N ickel catalysts are usually paired with "hard"nucleophiles,which attackt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…[1] The use of organolithium as an ucleophilic partner in the transition metal (TM)-catalyzed cross-coupling can be traced back to 1975, when Murahashi et al reported the first reactionb etween organolithiuma nd an organic halide catalyzed by Pd. [6] Ar emarkable improvement in the applicability of organolithium for cross-coupling reactions was achieved in 2013, when Feringae ta l. re-examined the Murahashi coupling and optimized both the selectivity (versus the lithium-halogen exchange) and efficiency. [6] Ar emarkable improvement in the applicability of organolithium for cross-coupling reactions was achieved in 2013, when Feringae ta l. re-examined the Murahashi coupling and optimized both the selectivity (versus the lithium-halogen exchange) and efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The use of organolithium as an ucleophilic partner in the transition metal (TM)-catalyzed cross-coupling can be traced back to 1975, when Murahashi et al reported the first reactionb etween organolithiuma nd an organic halide catalyzed by Pd. [6] Ar emarkable improvement in the applicability of organolithium for cross-coupling reactions was achieved in 2013, when Feringae ta l. re-examined the Murahashi coupling and optimized both the selectivity (versus the lithium-halogen exchange) and efficiency. [6] Ar emarkable improvement in the applicability of organolithium for cross-coupling reactions was achieved in 2013, when Feringae ta l. re-examined the Murahashi coupling and optimized both the selectivity (versus the lithium-halogen exchange) and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[2] However,s ince then, the utilization of organolithium in modern TM-catalyzed cross-coupling chemistry has been largely neglected, in favor of organoboron (Suzuki-Miyaura reaction), organozinc (Negishi reaction), organomagnesium (Kumada-Tamao reaction), and organotin (Stille reaction) reagents, [3] despite many advantages of organolithium compounds including low cost, commercial availability,a nd facile accessibility.The major problem that restricts the applicability of ac ross-coupling with organolithium is the competing lithium-halogen exchange (dehalogenation), which is usually quite fast and, thus, lowerst he selectivity.I nr ecent years, new approaches for the Murahashi reactionh ave been reported, such as the usage of af low microreactor for the biaryl coupling, [4] roundaboutr outes with stoichiometric silicon or boron-based transfer agents, [5] or ap rotocolt hat uses an in situ deprotonation. [6] Ar emarkable improvement in the applicability of organolithium for cross-coupling reactions was achieved in 2013, when Feringae ta l. re-examined the Murahashi coupling and optimized both the selectivity (versus the lithium-halogen exchange) and efficiency. [7] Since then, several new protocols for Murahashi couplings have been reported, enablingr eactions between various types of organolithium compounds and halides.…”
Section: Introductionmentioning
confidence: 99%
“…Although transition mental-catalyzed allylic substitution reactions employing various nucleophilic or electrophilic allylic precursors have been extensively studied [8][9][10], limited strategies were reported for their application in the C(sp 3 )-H allylic functionalization of 2-alkylazaares. Due to the high pKa value of alkyl azaarenes, the functionalization of benzylic C(sp 3 )-H was challengeable and pre-activation of the benzylic proton with suitable Lewis acids was often required prior to deprotonation of the alkyl chain by a stoichiometric base (Scheme 1a) [11][12][13][14][15][16]. In most cases, super stoichiometric amounts of strong bases, such as n BuLi or LiHMDS, would be used, which severely limited their applications.…”
Section: Introductionmentioning
confidence: 99%